Strategic Analysis and Its Role in Formulating Appropriate Future Strategies - Abbas Fadhil Mohsin Al-Shammari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Strategic analysis is the process of conducting research, collecting information, and conducting scientific analyses of that information in the business environment in which the organization operates and identifying the internal and external environmental factors of the organization in order to formulate the required and appropriate strategy. There are different methods of strategic analysis to determine and evaluate the organization's outputs, for example, or to determine the characteristics of the organization's strategic position or to determine long-term goals or to strengthen the organization's competitiveness, as it helps the organization to predict the future, etc. The importance of the research lies in highlighting that choosing the correct or required strategy, with a presentation of how to formulate and present appropriate strategies in private organizations, which is done through strategic analysis of all environmental conditions and the importance of implementing them by adopting strategic tools, techniques and methods in order to achieve the desired strategy while taking into account an environment full of major technological, scientific and economic changes in the market and economy. One of the most important results reached by the research is that the strategic analysis of the organization helps in defining and modifying its message and objectives and helps in developing and improving its performance. Therefore, it is one of the most important recommendations that organizations must adhere to when they want to choose future and new strategies. The research concluded that the strategic analysis of the organization is necessary in choosing future or new strategies.